A Collaborative Initiative For the Containment of Antimicrobial Resistance in Mexico. (24th November 2014) - Zaidi, Mussaret B.; Dreser, Anahi; Figueroa, Inda Marcela
Summary: Antimicrobial resistance exacts worldwide an increasingly significant clinical and economic toll. Despite the international calls for urgent action, antimicrobial use and resistance have been low on the Mexican government's policy agenda. In early 2010, a multidisciplinary group of experts launched a national initiative for containment of antimicrobial resistance that was endorsed by major medical, veterinary and public health institutions. The initiative called for seven priority actions including the creation of an ad hoc intersectoral advisory group, a requirement that human and veterinary antibiotics be dispensed only with prescription, and the establishment of effective surveillance systems. A consensus document was disseminated among key decision‐makers at the ministries of Health and Agriculture and the legislature. The Ministry of Health (MoH) enacted a decree effective as of August 2010, which enforced the regulations that required medical prescriptions for the sale of human antibiotics. While the information disseminated by the MoH did focus on the dangers of self‐medication, it failed to highlight the inherent perils of antibiotic resistance or the consequences of antibiotic use in food‐animals. Following the decree, there was a surge of medical offices controlled by retail pharmacies. In the veterinary sector, voluntary guidelines were developed for good husbandry practices, including antibiotic use in food animals; five antimicrobials for use in food‐animals were banned. No intersectoral advisory group or surveillance systems were established. This study describes a bottom‐top approach in Mexico for the development of a national strategy to improve antibiotic use and contain antimicrobial resistance. Its experiences suggest that, in countries such as Mexico that lack strong regulatory systems and surveillance capacities, a more systemic approach is warranted. Future efforts should begin with early involvement of key stakeholders and informing policy makers, professionals and the population at large about the critical importance of antibiotic resistance.